Caging and excited state emission of ICN trapped in cryogenic matrices: Experiment and theory - Helbing, J. (2000)
We discuss the cage induced stabilisation of fragments in excited electronic states following the UV-dissociation of ICN in cryogenic matrices. Emission spectra recorded upon A-band excitation of ICN in solid neon, argon and krypton exhibit a long progression of broad bands due to a weakly bound electronically excited state, presumably one of the low-lying triplet states 3Π1 or 3Π2 of ICN. A lifetime analysis favours the 3Π2 state. Molecular dynamics with quantum transitions (MDQT) simulations were conducted on six coupled electronic potential energy surfaces in a matrix of 498 argon atoms. Although a complete potential energy surface for the 3Π2 state is not available, it is known to be very similar to the 3Π1 one. Therefore only the 6 available [3Π1 (A', A''), 3Π(o)+, 1Π1 (A', A''), X 1Σ+] ab initio electronic potential energy surfaces were considered. The results predict a 2% probability of stabilisation in the shallow minimum of the triplet excited state. The molecule adopts a linear ICN configuration with a mean value of the I-CN distance far away from the absorption Franck-Condon region. The simulations also deliver insight into the mechanism of cage-induced population trapping in excited state surfaces, which is not accessible in the gas phase.